Hubungan Konsumsi Sugar Sweetened Beverage, Aktivitas Fisik dan Tingkat Stres dengan Kejadian Prediabetes - Sabrina, Sabrina; Komaruddin, Siska Ramdhani; Fikri, Al Mukhlas (Peneliti.net, 2024)
According to Riskesdas in 2018, the prevalence of prediabetes in Indonesia reached 26,3% of the adult population. An increase in blood sugar can be caused by consuming foods or drinks with high sugar, physical activity, stress factors, smoking habits and alcohol consumption. This study aims to analyze the relationship between sugar sweetened beverage consumption habits, physical activity and stress levels with the incidence of prediabetes in adults in Sukaluyu Village. This research uses a cross sectional design. The sample was determined using a purposive sampling technique of 81 respondents. Consumption of sugar sweetened beverages using the SQ FFQ form, physical activity using the GPAQ form and stress levels using the DASS 42 form. The results showed that there was no relationship between the habit of consuming sugar sweetened beverages (p-value=0,120), physical activity (p-value=0,713) and stress level (p-value=0,324) with fasting blood sugar levels as indicators of prediabetes. The conclusion of this study is that there is no significant relationship between sugar sweetened beverage consumption habits, physical activity and stress levels with the incidence of prediabetes in adults in Sukaluyu Village.